Muscular Dystrophies - Sakuma, Kunihiro (IntechOpen, 2019)
Skeletal muscle is a highly plastic organ that is modulated by various pathways controlling protein turnover. Muscle loss is common in muscular dystrophy, in which marked loss of various proteins such as the dystrophin-glycoprotein complex occurs around muscle fibers. This book provides a comprehensive overview of the various muscular dystrophies, including characteristics, diagnosis, and classification. General treatment of drugs (e.g. corticosteroids) and physical therapy for muscular dystrophies are discussed. In addition, current applications for cell and tissue engineering using muscle stem cells or gene therapy are introduced. This book also deals with the recent advances in appropriate models of drug screening using cell cultures or mammalian organs in vitro in this field.